Examining Vision Sharing as a Driver of Organizational Resilience: Evidence from Public Sector Contexts in Developing Economies - Muhammad Zaurez Afshar; Dr. Mutahir Hussain Shah (Indus Journal of Social Sciences, 2025)
Background: Public Sector entities in the developing economies are susceptible to shocks through the risk factors as determined by political instability, fiscal discipline and inefficient systems. In this regard, organizational resilience has become a very significant capacity of maintaining institutional performance. Purpose: The paper discusses the role of vision sharing in enhancing organizational resilience in the case of the public sector organizations based in developing economies. It would seek to integrate existing empirical and theoretical knowledge in formulating a conceptual framework of thinking about it which would be contextual. Approach: Narrative synthesis approach was adopted and the framework used was four stages proposed by Popay. Thematic analysis of relevant literature addressing organizational studies, leadership theory, and public administration was performed through systematic review, coding, and identification of causal linkages, mediating factors and transcending dynamics. Results: The study concluded that vision sharing can increase resilience in three interconnected pathways, including strategic alignment, adaptive engagement, and culture integration. Leadership style, institutional structure and political context moderate these effects. Implications: The study provides a vision-driven resilience-enabling policy insight and conceptual model to enable the leaders in the public sector to integrate resilience strategies. It also addresses research gaps in theory development and measurement.